Pengaruh Metode Demontrasi Terhadap Hasil Belajar pada Pembelajaran Matematika di SDN Banyubunih 1 - Angel Anastasia Kristianty Saragih (Jurnal Kajian dan Penelitian Umum, 2023)
The purpose of this study was to find out the problems in mathematics at the elementary level. One of the problems found is that there are still some students who have not mastered numeracy material, so research is needed to examine this. This type of research is Classroom Action Research (CAR). The method used in this study is the demonstration method. By using intrusmen Data collection in the form of interviews, documentation and tests. The data analysis technique used is completeness analysis.